About the existence of a horizontal mental pitch line in non-musicians. Issue 2 (3rd March 2020) - Guilbert, Alma
ABSTRACT: Pitch height is thought to be mentally represented along the vertical and the horizontal axes. This is based on a well-described effect: the Spatial Pitch Association of Response Codes (SPARC) effect. A low pitch is more easily associated with a left or a low location and a high pitch with a right or a high location. While much of the evidence supports the existence of these two "mental pitch lines" in musicians, the existence of a horizontal "mental pitch line" in non-musicians is much debated. The aim of the present study was to determine if the existence of a horizontal SPARC effect in non-musicians corresponds to a true tendency to represent pitch as ordinal information on a horizontal line. In two experiments with pitch-comparison tasks, a horizontal SPARC effect was replicated in non-musicians but was more in accordance with a dichotomous space-pitch association than with a true "mental pitch line". The SPARC effect cannot be considered as a proof of a real horizontal "mental pitch line" in non-musicians.